Daily gridded soil moisture simulations on a 1 km resolution grid covering Baden-Württemberg - Tijdeman, Erik; Menzel, Lucas (Universität, 2021)
The dataset contains gridded daily soil moisture simulations for Baden-Württemberg. The simulations were caried out with the hydroloigcal model TR...
Grant information: Research Network Water by the Ministry of Science, Research, and the Arts of the German Federal State of Baden‐Württemberg
Kind of data: Soil moisture simulations and animations
Gesehen am 03.03.2021
Keywords: Forschungsdaten; Datenbank